2002
DOI: 10.1016/s0031-9384(02)00911-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases and light: unlikely partners in a receptor localization puzzle

Abstract: Brief flashes of light directed at neuronal cell bodies and proximal dendrites of neurons in culture can enhance whole-cell electrophysiological responses mediated by NMDA and GABA A receptors. In experiments aimed at identifying the molecular moieties responsible for mediating this phenomenon, we observed that broad-spectrum protein kinase inhibitors substantially amplified the actions of light. Kinase inhibitors, however, were surprisingly ineffective in altering light-induced potentiation of recombinant NMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…As we have proposed before, modulation of ion channel function by both redox agents and light seem to be structurally linked within the receptor (Leszkiewicz & Aizenman, 2002). Specifically, we have shown that both GABA and NMDA receptor mediated responses are enhanced following exposure to light stimuli, and that reducing agents occlude the effects of light on these channels (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…As we have proposed before, modulation of ion channel function by both redox agents and light seem to be structurally linked within the receptor (Leszkiewicz & Aizenman, 2002). Specifically, we have shown that both GABA and NMDA receptor mediated responses are enhanced following exposure to light stimuli, and that reducing agents occlude the effects of light on these channels (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…GABA A receptors have been shown to be redox sensitive (Pan et al ., 1995; Amato et al ., 1999; Pan et al ., 2000), and we have reported that an intact and oxidized functional redox site is necessary for the light induced potentiation of NMDA induced currents (Leszkiewicz & Aizenman, 2002). Therefore, we evaluated whether the effects of light would also be altered by the oxidation or reduction of recombinant α 1 β 2 GABA A receptors transfected in CHO cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations